On the Optimal Recovery of Integrals of Set-Valued Functions - Babenko, V. F.; Babenko, V. V.; Polishchuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider the problem of optimization of the approximate integration of set-valued functions from the class specified by a given majorant of their moduli of continuity performed by using the values of these functions at n fixed or free points of their domain.